Pengujian model kesejahteraan keuangan : Studi komparasi masyarakat berpenghasilan tinggi dan rendah - Shintani, Nadella Putri; Iramani, Rr; Lutfi (Jurnal Ilmu Manajemen, 2025)
Financial well-being is one of the most critical issues in financial research. Financial well-being is when a person feels comfortable and satisfied and does not feel depressed or worried about their financial condition. The study examines the effect of financial knowledge and experience on the financial well-being of high and low-income communities. The sample was taken using purposive sampling. Data is collected using a survey method, and questionnaires are distributed to respondents according to the criteria. The data analysis used is SEM-PLS.  The results of this study prove that financial experience has a positive effect on financial well-being, while financial knowledge has no impact on financial well-being. Another interesting finding of this study is that financial behaviour can mediate the effects of financial experience on financial well-being in both high and low-income communities. This result implies that people should improve their financial expertise to improve their financial well-being. High financial experience supported by good financial behaviour will give a person a high perception of financial well-being because of a sense of satisfaction and comfort and the ability to not feel worried or depressed about their financial condition.